A grand mimicker of pulmonary malignancy: The massive mediastinal intercostal nerve tumour - Syed H. Haq; Claire Friederick; David Eapen; Sidra Shah; Hoshimjon Begmatov; F. N. U. Sandesh; Sreenivasa Chanamolu (Respirology Case Reports, 2024)
Abstract Mediastinal mass‐like manifestations often cause alarm and instigate a myriad of investigative testing to rule out insidious malignant processes. However, a unique and benign finding, the schwannoma can present either incidentally or while in pursuit of a symptomatic presentation. Given its rarity, limited literature exists on these neurogenic tumours with less than three dozen reported cases. No specific guidelines exist regarding the extent of required advanced imaging or degree of invasive evaluation. Therefore, practitioners confronted with these intrathoracic tumours may find management challenging or delayed. We present a case discussing a large benign tumour causing symptomatic burden, the investigative methods implored and treatment modality. We add to the literature another unique presentation of an intercostal nerve sheath tumour with schwannoma pathology.